2020
DOI: 10.1136/emermed-2019-208458
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital critical care is associated with increased survival in adult trauma patients in Scotland

Abstract: BackgroundScotland has three prehospital critical care teams (PHCCTs) providing enhanced care support to a usually paramedic-delivered ambulance service. The effect of the PHCCTs on patient survival following trauma in Scotland is not currently known nationally.MethodsNational registry-based retrospective cohort study using 2011–2016 data from the Scottish Trauma Audit Group. 30-day mortality was compared between groups after multivariate analysis to account for confounding variables.ResultsOur data set compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
3
34
1
2
Order By: Relevance
“…This allows for advanced resuscitation and earlier provision of hospital-based care, reducing the therapeutic vacuum that exists outside of the hospital setting. Literature focused on physician-augmented HEMS models suggest a possible mortality benefit in trauma patients when compared to ground EMS [3,4]. However, these data are derived from low quality studies with significant heterogeneity [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for advanced resuscitation and earlier provision of hospital-based care, reducing the therapeutic vacuum that exists outside of the hospital setting. Literature focused on physician-augmented HEMS models suggest a possible mortality benefit in trauma patients when compared to ground EMS [3,4]. However, these data are derived from low quality studies with significant heterogeneity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Physician-augmented HEMS systems allow for advanced trauma procedures beyond the critical care paramedic or nurse scope, including finger thoracostomy, resuscitative thoracotomy, lateral canthotomy, and limb amputation [4,6]. Beyond trauma care, pre-hospital physician delivery to resource-limited centres for inter-facility transport can allow for advanced medical interventions, such as difficult airway management, transvenous pacemaker insertion, linton tube placement, and central venous and arterial line insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Motor vehicle accidents often result in severe trauma, which places the victim at high risk for death due to airway complications, chest injuries, and hemorrhagic shock [7]. Optimal management includes transporting the patient to the nearest trauma center as quickly and safely as possible for definitive trauma care.…”
Section: Discussionmentioning
confidence: 99%
“…While literature about ECTs in the U.S. is scarce, studies in European countries have found evidence in favor of physician-assisted response teams. Maddock et al discovered in Scotland that physician-led prehospital critical care teams (PHCCTs) resulted in reduced mortality in trauma patients, even when considering that patients who required PHCCTs generally had higher injury severity scores (ISS) [7]. Smith et al performed a study in the United Kingdom and were the first able to discern a risk-adjusted mortality benefit in patients treated by ECTs with no increase in morbidity [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, major trauma remains a relatively rare cause of death within England and Wales. In Scotland paramedic exposure to trauma accounts for 0.3% of case volume [ 3 ]. The lack of exposure to major trauma can cause anxiety and our perception of what is classified as major trauma is potentially complex.…”
Section: Introductionmentioning
confidence: 99%